Evaluasi Program Nasional Upaya Khusus Sapi Indukan Wajib Bunting (Upsus Siwab) di Kota Tanjungpinang - SRI AMBAR RINAH; Diah Siti Utari; Nurmarlina (STISIPOL Raja Haji, 2021)
The State of Indonesia is an agrarian country, which mostly seeks as farmers and ranchers. However, Indonesia has not been able to meet the needs of beef for the community. Though demand for beef continues to increase from time to time in line with increasing population growth. Therefore, to overcome this problem, the government made a national program that is a special effort for pregnant cattle breeders (Upsus Siwab), which is stated in Minister of Agriculture Regulation No. 48 / Permentan / PK.210 / 10/2016 concerning special efforts to accelerate the increase pregnant cattle and buffalo populations. For the city of Tanjungpinang, the national program Upsus Siwab focuses more on the target of increasing population through artificial insemination. This study aims to determine the process and results of the implementation of the national program for the special effort of mandatory breeding cattle (Upsus Siwab) in the city of Tanjungpinang, using the CIPP evaluation model proposed by Stufflebeam and Shinkfield. This type of research is exploratory with a qualitative approach. Then the techniques and data collection tools are carried out by means of observation, interviews, and documentation. The research locations in the Department of Agriculture and Fisheries and five groups of fostered cattle from the Department of Agriculture and Fisheries of Tanjungpinang city are one of the target groups of the program. The results of the study indicate that the national program of Upsus Siwab in Tanjungpinang City has been implemented well, but with existing limitations. Because the components of the availability of facilities and infrastructure, namely facilities and budget are still inadequate.So there are still many obstacles that must be faced. The suggestions that the author can convey so that the policy implementers do a comprehensive outreach to groups and individual breeders in the city of Tanjungpinang. As well as the Tanjung Pinang city government to allocate a special budget for animal husbandry development in the city of Tanjungpinang, this is so that the implementation of the Upsus Siwab national program will continue without any limited facilities and infrasctructure.